Strategi Komunikasi Pemasaran Asmara Coffee Melalui Event Musik Asmaraloka Dalam Menciptakan Brand Awaraness - Setiawan, Abdul Lafif; Soraya, Iin; Ekowati, Sari (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this study is to analyze Asmara Coffee's marketing communication strategy through the Asmaraloka music event in creating and increasing brand awareness among consumers. This study uses a constructivism paradigm with a qualitative approach to analyze Asmara Coffee's marketing communication strategy through the Asmaraloka music event in increasing brand awareness. Data were collected through interviews, observations, literature studies, and documentation, with analysis using the interactive method of Miles and Huberman and verification through triangulation. The results of the study provide an in-depth picture of the effectiveness of the marketing strategy implemented and its impact on Asmara Coffee's brand awareness. Research on Asmara Coffee shows that tight competition in the coffee shop industry is a challenge for Asmara Coffee to stay competitive and increase brand awareness. Asmara Coffee strives to maintain its existence by optimizing social media accounts, providing the best service, and routinely holding music events. The Asmaraloka music event is the main strategy in attracting new consumers and strengthening brand awareness. Through this approach, Asmara Coffee strives to remain relevant and competitive amidst business competition.